2022
DOI: 10.3389/fendo.2022.1028114
|View full text |Cite
|
Sign up to set email alerts
|

Triple drug therapy with GABA, sitagliptin, and omeprazole prevents type 1 diabetes onset and promotes its reversal in non-obese diabetic mice

Abstract: Previous studies have reported that dual drug combinations consisting of γ-aminobutyric acid (GABA) together with a dipeptidyl-peptidase-4 inhibitor (DPP-4i), also a DPP-4i with a proton pump inhibitor (PPI), could improve pancreatic β-cell function and ameliorate diabetes in diabetic mice. In this study, we sought to determine if a triple drug combination of GABA, a DPP-4i and a PPI might have superior therapeutic effects compared with double drug therapies in the prevention and reversal of diabetes in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
4
0
2
Order By: Relevance
“…The above clinical outcomes reported here are consistent with our findings in a recent study of this combination of GABA, a DPP-4i, and a PPI in NOD mice, an animal model for human T1D ( 16 ). Importantly, the combination of all three drugs prevented and reversed autoimmune diabetes in the NOD mice, whereas all two-drug combinations were less or not effective.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The above clinical outcomes reported here are consistent with our findings in a recent study of this combination of GABA, a DPP-4i, and a PPI in NOD mice, an animal model for human T1D ( 16 ). Importantly, the combination of all three drugs prevented and reversed autoimmune diabetes in the NOD mice, whereas all two-drug combinations were less or not effective.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it was reported that the combination of GABA and GAD-alum, in a 12-month, double-blind, randomized T1D pediatric trial, significantly reduced fasting and meal-stimulated serum glucagon, but preservation of the C-peptide response was not attained, however the safety of GABA was confirmed ( 15 ). We have recently reported that a three-drug combination therapy consisting of the neurotransmitter GABA, a DPP-4i and a PPI can prevent and reverse diabetes in non-obese diabetic (NOD) mice, an animal model for human T1D, whereas all two-drug combinations were less or not effective ( 16 ). The objective of the study reported here was to determine whether glycemic control in patients with T1D could be improved by adding a combination of GABA, DPP-4i, and PPI to a standard insulin treatment regimen in these patients, in a real-world clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…In nonobese diabetic mice, normoglycemia was shown to be restored when sitagliptin and omeprazole were combined, increasing the synergistic effect of the two medications. 29 Pantoprazole ✓ According to a recent study, sitagliptin and pantoprazole are well tolerated, safe, and may help certain islet transplant recipients who had early graft insufficiency regain their insulin independence. However, this improvement did not last once the medication was stopped.…”
Section: Drug-drug Interaction Commentmentioning
confidence: 99%
“…For example, it has been reported that the combination therapy of GLP-1 receptor agonists (exendin-4) and PPI (omeprazole) is closely related to the enhanced insulin sensitization actions in streptozotocin (STZ)-induced T1D model mice ( 70 ). The study found that triple drug therapy with GABA, DPP-4 inhibitors (sitagliptin), and PPI (omeprazole) has an encouraging therapeutic effect in ameliorating β cell function and managing T1D in non-obese diabetic (NOD) mice ( 71 ). In the STZ-induced young and old diabetic mice models, the drug combination therapy consisting of melatonin and DPP-4 inhibitors (sitagliptin) could effectively provoke β cell proliferation in mice, and then ameliorate diabetic manifestations by reducing fasting blood glucose levels, enhancing glucose tolerance, and plasma insulin levels ( 72 ).…”
Section: Drug Combination Therapy For Diabetesmentioning
confidence: 99%